Advanced Diagnostic Techniques in Autoimmune Bullous Diseases - Jindal, Anuradha (Indian J Dermatol, 2017)
Autoimmune blistering diseases are diverse group of conditions characterized by blisters in the skin with or without mucosal lesions. There may be great degree of clinical and histopathological overlap; hence, advanced immunological tests may be necessary for more precise diagnosis of these conditions. Direct immunofluorescence microscopy is the gold standard tests to demonstrate the tissue-bound antibodies and should be done in all cases. Magnitude of antibody level in patient’ serum can be assessed by indirect immunofluorescence and enzyme linked immunosorbent assay. In this article we have reviewed the various techniques that are available in the diagnosis of autoimmune blistering diseases.